Can Hospital Competition Really Affect Hospital Behavior or Not? An Empirical Study of Different Competition Measures Comparison in Taiwan - Tsung-Hsien Yu PhD; Yu-Chi Tung PhD; Chung-Jen Wei PhD (SAGE Publishing, 2017)
Different approaches to measure the hospital competition index might lead to inconsistent results of the effects of hospital competition on innovation adoption. The purpose of this study is to adopt a different approach to define market area and measure the level of competition to examine whether hospital competition has a positive effect on hospital behavior, taking quality indicator projects participation as an example. A total of 238 hospitals located in Taipei, Taichung, and Kaohsiung were recruited in this study. Competition index was used as the independent variable, and participation lists of Taiwan Clinical Performance Indicator and Taiwan Healthcare Indicator Series in 2012 were used as dependent variables. All data used in this study were retrieved from the 2012 national hospital profiles and the participation list of the 2 quality indicator projects in 2012; these profiles are issued by the Taiwan Ministry of Health and Welfare annually. Geopolitical boundaries and 4 kinds of fixed radiuses were used to define market area. Herfindahl-Hirschman Index and hospital density were used to measure the level of competition. A total of 12 competition indices were produced in this study by employing the geographic information system, while max-rescaled R 2 was used to evaluate and compare the models on goodness of fit. The results show that the effects of hospital competition on quality indicator projects participation were varied, which mean different indicators for market competition might reveal different conclusions. Furthermore, this study also found the Herfindahl-Hirschman Index at 5-km radius was the optimum competition index.